2005
DOI: 10.1080/08035250500277101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on inflammatory markers and renal functions

Abstract: Inflammatory mediators increased significantly in obese children, and the glomerular filtration rate increased as the body mass index increased. To prevent obesity-related complications in adulthood, it is important to take measures to prevent development of obesity during childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 24 publications
(20 reference statements)
6
17
0
1
Order By: Relevance
“…Though the composition and concentration of urine vary with physiologic state, there was less than 10±10% (mean±standard deviation) difference in total protein abundance among individual specimens, as ascertained by using gel image densitometry (Fig. 1), similar to earlier studies of urine of children [2830]. …”
Section: Resultssupporting
confidence: 83%
“…Though the composition and concentration of urine vary with physiologic state, there was less than 10±10% (mean±standard deviation) difference in total protein abundance among individual specimens, as ascertained by using gel image densitometry (Fig. 1), similar to earlier studies of urine of children [2830]. …”
Section: Resultssupporting
confidence: 83%
“…An increased GFR was observed in overweight compared with lean subjects, being significantly positively related to BMI [44] and insulin resistance [18]. …”
Section: Obesity-related Renal Injury In Childhoodmentioning
confidence: 99%
“…While the relation between obesity and both raised C-reactive protein (CRP) [4,5] and decreased adiponectin (including high-molecular-weight adiponectin) levels [6,7,8,9,10] in children is well documented, studies examining IL-6 levels in overweight children show conflicting findings [8,11,12,13]. Obese prepubertal Turkish children have significantly elevated IL-6 levels compared to lean controls [11], and Herder et al [12] showed a significant association between IL-6 levels and BMI (adjusted for age, sex and lipids) in a large cohort of German adolescents.…”
Section: Introductionmentioning
confidence: 99%